Association between Breakfast Nutritional Contribution and Body Mass Index of IPB University Postgraduate Students - Rif’atul Amini; Andi Rahmad; Arin Tria Agustin; Ramadhani Fitri; Hardinsyah Hardinsyah (Universitas Teuku Umar, 2022)
Breakfast is one of the habits that contribute to fulfilling daily energy intake and reducing the risk of obesity. This study aimed to analyze the association between breakfast nutritional contribution and body mass index (BMI) of IPB University nutrition postgraduate students. The research applied a cross sectional study design for all 36 postgraduate nutrition students of IPB University. Data collected include socio-demographic, body weight and height, and food consumption, which gained by applying 1x24 hours food recall method. The intake of energy, protein, carbohydrate, fat, fiber, water, vitamin A, D, E, C, B1, B2, B3, B6, B9, B12, and calcium, iron, as well as zinc calculated using Nutrisurvey 2007 version. The data were analyze by applying Spearman test. The results showed that there was a significant negative association between the breakfast contribution of energy (p= 0.029, r= -0.364), protein (p= 0.013, r= -0.410), fat (p= 0.049, r= -0.331), vitamin B2 (p= 0.033, r= -0.357), and vitamin B12 (p= 0.007, r= -0.443) with BMI. In conclusion, the higher the contribution of major nutrient for breakfast, the lower the BMI.